The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1159/000107384
|View full text |Cite
|
Sign up to set email alerts
|

Action on Vascular Risk Factors: Importance of Blood Pressure and Lipid Lowering in Stroke Secondary Prevention

Abstract: Introduction: Secondary stroke prevention comprises a broad spectrum of therapeutic actions that includes the appropriate management of risk factors and the action on blood pressure and serum lipids that are of great importance to decrease stroke recurrences. Methods: We conducted a review of the published studies analyzing the relevance of the treatment of blood pressure and serum lipids, with special attention to recent findings of clinical trials and current guidelines on stroke secondary prevention. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 189 publications
0
5
0
Order By: Relevance
“…We did not adjust for stroke severity, treatment received during the index hospitalization or medications and lifestyle factors following stroke [15,16,17] in the primary analyses, since these factors may be downstream consequences occurring after the development of reduced or highly elevated eGFR. In sensitivity analyses we additionally controlled for correlates of stroke severity.…”
Section: Methodsmentioning
confidence: 99%
“…We did not adjust for stroke severity, treatment received during the index hospitalization or medications and lifestyle factors following stroke [15,16,17] in the primary analyses, since these factors may be downstream consequences occurring after the development of reduced or highly elevated eGFR. In sensitivity analyses we additionally controlled for correlates of stroke severity.…”
Section: Methodsmentioning
confidence: 99%
“…In primary prevention there may be marginal cerebrovascular benefits for regimens that include an angiotensin-converting inhibitor, an angiotensin II type-1 receptor blocker and calcium channel blocker, but the available data are not definitive. Although it is acknowledge that new studies are needed to asses whether a specific drug regimen is better than the other, for secondary prevention, current guidelines recommend the use of diuretics and the combination of angiotensin-converting inhibitors and diuretics or angiotensin II receptor blockers to reduce stroke recurrence [5,71,72].…”
Section: Resultsmentioning
confidence: 99%
“…All forms of arterial hypertension, i.e. isolated systolic and diastolic hypertension, and their combinations increase stroke risk [5].…”
Section: Primary Prevention Of Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Dyslipidemia is a recognized risk factor for coronary arterial disease, but its role as a risk factor for stroke has been controversial for a long time [1]. Prior observational cohort studies showed no clear relationship between serum cholesterol and stroke.…”
Section: Dyslipidemia As Stroke Risk Factormentioning
confidence: 99%